Amendments mediated iron immobilization under different moisture regimes in metal contaminated soil - Nogiya, Mahaveer; Dwivedi, B S; Datta, S P; Meena, M C; Das, T K; Dey, Abir; Samal, S K; Choudhary, Mahipal; Sharma, G K; Kumar, Ashok (The Indian Journal of Agricultural Sciences, 2020)
The present study was performed to evaluate the effect of lime, poultry manure and farmyard manure (FYM) application on the immobilization of soil iron (Fe) under both submergence and alternate wetting-drying (AWD) soil moisture regimes. Effect of soil amendments (organic and inorganic) and soil moisture regimes on the dry matter yield, total Fe content in plant, the DTPA-extractable soil Fe and the distribution of Fe in various chemical fractions of contaminated soil was explored in the greenhouse pot experiment during 2018 at IARI, New Delhi. Results indicated that the mean DTPA-extractable Fe content in post-harvest soil was found significantly lower under AWD (84.8 mg/ kg) as compared to submergence (118 mg/kg). The mean DTPA-extractable Fe was significantly reduced by 14.7% due to the application of lime over control. Poultry manure and FYM application were ineffective in altering the mean DTPA-extractable Fe. Water soluble and exchangeable Fe content in post-harvest soil was decreased significantly by 17.7% under AWD compared with submergence and it was reduced significantly by 25.2% due to the lime application over control. Whereas, carbonate bound Fe content was increased significantly by 8.0% due to the lime application over control while it was decreased significantly by 5.3% due the poultry manure over control. Therefore, lime application under AWD soil moisture regime was the best practice for remediation of metal contaminated soil and poultry manure and FYM could be include in management practices for improving crop yield.